A Two-Level Factorial Design for Screening Factors that Influence the Growth of Pseudomonas sp. Strain Dry135 on Acrylamide (Journal of Environmental Microbiology and Toxicology, 2022)
Polyacrylamide is one of the most important sources of acrylamide in soil because it degrades into acrylamide over time. The breakdown of acrylamide by bacteria has experienced a steady but consistent increase in interest all over the world as a bioremediation technique. In this investigation, a previously obtained molybdenum-reducing bacterium with amide-degrading capabilities was found on critical parameters leading to optimum growth on acrylamide utilizing a two-level factorial design. The two-level factorial design was used in the screening of five independent parameters impacting the bacterium's growth on acrylamide. These variables include pH, temperature, incubation period, acrylamide concentration, and ammonium sulphate concentration. The two-factor factorial design was successful in identifying major contributing parameters in the growth of this bacterium on acrylamide, which were acrylamide concentration, pH, and incubation time (p
Keywords: Acrylamide; Pseudomonas sp.; Bioremediation; Screening; Two-Level Factorial Design